Cross‐Language Activation Begins During Speech Planning and Extends Into Second Language Speech. Issue 2 (8th October 2015) - Jacobs, April; Fricke, Melinda; Kroll, Judith F.
Abstract: Three groups of native English speakers named words aloud in Spanish, their second language (L2). Intermediate proficiency learners in a classroom setting (Experiment 1) and in a domestic immersion program (Experiment 2) were compared to a group of highly proficient English–Spanish speakers. All three groups named cognate words more quickly and accurately than matched noncognates, indicating that all speakers experienced cross‐language activation during speech planning. However, only the classroom learners exhibited effects of cross‐language activation in their articulation: Cognate words were named with shorter overall durations, but longer (more English‐like) voice onset times. Inhibition of the first language during L2 speech planning appears to impact the stages of speech production at which cross‐language activation patterns can be observed. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki